Study of Cultural Marketing Behavior of Tourists: Case Study of Floating Market Tourism in Nakhon Pathom Province - boonmalert, Wiriya; Thongrawd, Chairit (Journal of Management Science Nakhon Pathom Rajabhat University, 2020)
This study has the following objectives: (1) To study the behaviors and satisfaction of tourists towards cultural tourism: a case study of floating markets tourism in Nakhon Pathom Province; (2) To compare behaviors and satisfaction of tourists towards cultural tourism: a case study of floating markets tourism in Nakhon Pathom Province. The research is a mixed research between quantitative and qualitative research emphasizing quantitative research as a principle research. The sampling used is an accidental sampling. Research tools used are questionnaire and qualitative research used semi-structural in-depth interviews. Statistics used for analysis in the research are frequency counts, percentage, average, and standard deviation. The research results found that: (1) The behaviors and satisfaction of the tourists towards cultural tourism: a case study of floating markets tourism in Nakhon Pathom Province, in general, was at a mid-level; and when considered by aspects, it was found that motivation was at a mid-level in all aspects, in this order: traveling, tourism attractiveness, servicing, facilities, and public relations; (2) comparison of behaviors and satisfaction of tourists towards cultural tourism: A case study of floating markets tourism in Nakhon Pathom Province, classified by personal factors, was found that tourists with different gender, age, education, profession, averaged monthly earning, and marital status, were statistically significant difference at .05 level; while tourists with different domicile had different levels of motivation in cultural tourism at a statistically significant level. Article history : Received 23 June 2019 Revised 1 April 2020 Accepted 4 April 2020 SIMILARITY INDEX = 0.00 %